2009
DOI: 10.1002/prca.200900001
|View full text |Cite|
|
Sign up to set email alerts
|

Bronchoalveolar lavage fluid proteomic patterns of sulfur mustard‐exposed patients

Abstract: Sulfur mustard is an alkylating agent that reacts with ocular, respiratory, cutaneous, and bone marrow tissues. Main late respiratory complications are chronic obstructive pulmonary disease, bronchiectasis, asthma, and bronchiolitis obliterans. The aim of the present study was to identify differentially expressed proteins in bronchoalveolar lavage (BAL) fluid of control healthy and sulfur mustard-exposed lung disease patients. The BAL protein profile of ten healthy and 30 exposed patients with mild, moderate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 38 publications
1
35
1
Order By: Relevance
“…Expression of S100A8 and S100A12 were both significantly increased in the PMN from the SM-exposed and COPD hosts. This was in keeping with our previous study on BAL fluid from SM exposed patients that also showed significant increases in S100A8 protein (Mehrani et al, 2009). S100A12 is constitutively expressed in PMN ($5% of cytosolic protein) and, as a calcium-, zinc-, and copper-binding protein, plays a prominent role in regulation of inflammatory processes and immune responses.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Expression of S100A8 and S100A12 were both significantly increased in the PMN from the SM-exposed and COPD hosts. This was in keeping with our previous study on BAL fluid from SM exposed patients that also showed significant increases in S100A8 protein (Mehrani et al, 2009). S100A12 is constitutively expressed in PMN ($5% of cytosolic protein) and, as a calcium-, zinc-, and copper-binding protein, plays a prominent role in regulation of inflammatory processes and immune responses.…”
Section: Discussionsupporting
confidence: 92%
“…Our own previous findings with SM-exposed patients revealed there were differing proteomic profiles between mild, moderate, and severe cases of exposure (Mehrani et al, 2009(Mehrani et al, , 2011. Specifically, proteomic analyses of bronchoalveolar lavage (BAL) fluids from SM-exposed patients indicated that PMN and S100A8 protein expression (mostly produced by PMN) were significantly increased in an exposure dose-related manner (Mehrani et al, 2009). Moreover, proteomic analyses of plasma from these patients revealed a significant increase in serum amyloid A1 (marker of systemic inflammation) as well (Mehrani et al, 2011).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations